Management accountants' roles and management controls in hospitals at times of strain — Experiences during the Corona pandemic - Jennifer Kunz; Laura Brix; Roberta Di Carlo; Jens O. Brunner (Journal of Management Control, 2025)
To gain insights into resilient action-taking in management accounting departments in the healthcare sector during times of crisis, this article investigates the reaction of these departments in German hospitals during the Corona pandemic. The analysis is based on qualitative data collected via semi-structured interviews with 21 senior management accountants in large German hospitals in 2020 and 2022. Findings are discussed against the background of a theory-driven resilience framework. The results indicate that hospitals' management accounting departments could quickly adjust their activities despite the absence of crisis plans for management accounting. They mainly contextualized the applied management controls in an enabling, complexity-absorbing way, and they acted as information providers and partly as business partners, but rarely as corporate policemen. These activities were embedded in four overarching topics that framed all their activities, i.e., the development of a mindset of adaptation, the will to keep the business going, and the reasonable shaping of internal and external interactions. These observations add insights to the empirical research on the effect of crises on management controls and management accountants' roles, and the developed resilience framework provides a structure to organize them beyond the present study to advance theory building.
Keywords: I18; M10; M41; 330; Corona pandemic; Health care system; Hospitals; Management controls; Management accounting